2016
DOI: 10.1039/c6nr04185j
|View full text |Cite
|
Sign up to set email alerts
|

Observation of antisite domain boundaries in Cu2ZnSnS4 by atomic-resolution transmission electron microscopy

Abstract: Atomic resolution transmission electron microscopy has been used to examine antisite defects in Cu2ZnSnS4 (CZTS) kesterite crystals grown by a hot injection method. High angle annular dark field (HAADF) imaging at sub-0.1 nm resolution, and lower magnification dark field imaging using reflections sensitive to cation ordering, are used to reveal antisite domain boundaries (ADBs). These boundaries, typically 5-20 nm apart, and extending distances of 100 nm or more into the crystals, lie on a variety of planes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 17 publications
7
44
0
Order By: Relevance
“…Antiphase domain boundaries are well established in bimetallic alloys (with the classic case of Cu 3 Au), although the effect of the diffraction is much different . Somewhat similar antiphase boundaries (stacking faults) have been reported but involve Sn site swapping with much larger domains .…”
Section: Resultsmentioning
confidence: 77%
“…Antiphase domain boundaries are well established in bimetallic alloys (with the classic case of Cu 3 Au), although the effect of the diffraction is much different . Somewhat similar antiphase boundaries (stacking faults) have been reported but involve Sn site swapping with much larger domains .…”
Section: Resultsmentioning
confidence: 77%
“…Formation of SFs was found in CZTS grown on single-crystal Si (111) wafers [21] and CZTS nanoparticles [22]. Another recent experimental study has shown that ADBs are formed abundantly in CZTS nanocrystals [23], possibly due to the low formation energy of antisite defect complexes in multicomponent semiconductors [2]. A density functional theory (DFT) calculation also shows that pre-existing defect complexes can lower the energy cost to form another defect complex in close configuration [24], providing a hint that point defects can be gathered and form a spatially extended defect.…”
Section: Introductionmentioning
confidence: 92%
“…Experimental evidence of faults in the layer with Cu and Sn has been provided [23], however, Cu and Zn are difficult to distinguish by transmission electron microscopy (TEM). Due to the larger chemical (size and charge) mismatch, the layer with Cu and Sn should be more rigid than the layer with Cu and Zn.…”
Section: Antisite Domain Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al showed by DFT Sb Sn exhibits smaller lattice relaxations and has lower formation energy than native CZTS defects [131]. It should be mentioned that Cu Sn and Zn Sn antisite domain boundaries have been experimentally observed by atomic resolution transmission electron microscopy in CZTS crystallites [132]. Furthermore, DFT supercell calculations by Chen et al concluded that such antisites give rise to mid-gap traps which could be highly detrimental to device performance [6].…”
Section: Germanium (Ge)mentioning
confidence: 99%